2021
DOI: 10.12659/ajcr.929816
|View full text |Cite
|
Sign up to set email alerts
|

A Prolonged Time to Diagnosis Due to Misdiagnoses: A Case Report of an Atypical Presentation of Eagle Syndrome

Abstract: Patient: Male, 23-year-old Final Diagnosis: Eagle syndrome Symptoms: Pain Medication: — Clinical Procedure: — Specialty: Dentistry • Pathology Objective: Unusual clinical course Background: Eagle syndrome is an unusual condition in which the styloid process (SP) becomes elongated and causes different clinical symptoms due to pressure on adjacent anatomical structures. The sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…1 Eagle's syndrome is often misdiagnosed due to its rarity and non-specific symptoms, and delay to diagnosis has been reported to be between 10 and 27 years. 1,3,4 In our case report, it took almost an year for the patient to be diagnosed correctly. Similarly, it has been reported that despite that the patient having knowledge of Eagle's syndrome, it took 4 years to reach the correct diagnosis due to the unusual presentation of his symptoms.…”
Section: Case Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…1 Eagle's syndrome is often misdiagnosed due to its rarity and non-specific symptoms, and delay to diagnosis has been reported to be between 10 and 27 years. 1,3,4 In our case report, it took almost an year for the patient to be diagnosed correctly. Similarly, it has been reported that despite that the patient having knowledge of Eagle's syndrome, it took 4 years to reach the correct diagnosis due to the unusual presentation of his symptoms.…”
Section: Case Discussionmentioning
confidence: 75%
“…Similarly, it has been reported that despite that the patient having knowledge of Eagle's syndrome, it took 4 years to reach the correct diagnosis due to the unusual presentation of his symptoms. 3 The lack of a clear aetiological link and the lack of knowledge about this clinical entity contribute to misdiagnosis. 1 Patients with severe calcification of the SP have also been reported to be asymptomatic.…”
Section: Case Discussionmentioning
confidence: 99%
See 3 more Smart Citations